Lipids and apolipoproteins C-III and E among treatment-naïve and treatment-experienced persons with HIV in Nigeria - Mercy N. Okunorobo; Nwakasi K. Nnamah; Ugomma A. Ude; Enyioma A. Ude (AOSIS, 2023)
Background: Dyslipidaemia is a known cause of cardiovascular mortality. Persons living with HIV are at high risk of developing cardiovascular disease due to lipid metabolism disorders associated with HIV or its therapy. Objective: This study evaluated concentrations of lipoproteins and apolipoprotein C-III and E, as a way of assessing cardiometabolic risks among HIV patients. Methods: We enrolled 50 HIV-negative persons and 100 HIV-positive patients, 50 on antiretroviral therapy (ART) and 50 treatment-naïve persons, from the Central Hospital and the Stella Obasanjo Hospital, Benin City, Edo State, Nigeria, between May 2015 and November 2015. Participants with a history of metabolic abnormalities were excluded. Apolipoproteins were assessed by enzyme-linked immunosorbent assay, while lipids were measured by spectrophotometry. Results: There were significant abnormalities in the lipid profile of patients with HIV. Triglycerides levels of HIV patients (ART-naïve: 1.44 ± 0.65 mmol/L; p  0.001 and ART-experienced: 1.49 ± 0.70 mmol/L; p = 0.001) were significantly higher than among controls (0.95 ± 0.54 mmol/L). HIV patients had higher concentrations of apolipoprotein C-III than controls (p  0.001) and higher low-density lipoprotein cholesterol levels (treatment-naïve: 2.83 mmol/L and ART-experienced patients: 3.59 mmol/L) than controls (2.50 mmol/L; p = 0.003). Conversely, HIV patients had significantly lowered high-density lipoprotein cholesterol levels compared to controls (p  0.001). Conclusion: Dyslipidaemia was observed among HIV participants, irrespective of their ART experience. Therefore, it is crucial that the lipids of HIV patients be closely monitored to enable early intervention and decrease cardiovascular death. What this study adds: This study affirms that dyslipidemia is a complication of HIV or the prolonged use of ART.